Storm surge and ponding explain mangrove dieback in southwest Florida following Hurricane Irma - David Lagomasino (Nature Portfolio, 2021)
Mangroves are adapted to cope with tropical storms, but might be threatened by rising frequency and intensity of these events. Here the authors document one of the largest mangrove diebacks on record following Hurricane Irma in Florida, and show a greater role of storm surge and ponding rather than wind as a mechanism for mangrove dieback.